Efficient Semi-Lagrangian Vlasov-Maxwell Simulations of High Order Harmonic Generation from Relativistic Laser-Plasma Interactions (Communications in Computational Physics, 2018)
We describe a relativistic semi-Lagrangian scheme for the numerical solutionof the relativistic Vlasov-Maxwell system. The implementation strategy on a modernnon-unified memory access (NUMA) architecture using the OpenMP frameworkis discussed. We demonstrated that close to perfect scaling can be obtained on modernmany-core, multi-socket systems. Application of this code to the problem of relativisticgeneration of high-harmonic laser radiation is demonstrated. The results are comparedto particle-in-cell (PIC) simulations, indicating in particular that for warm plasma theVlasov simulation is superior. We discuss the impact of plasma temperature on theradiation spectrum and show that the efficiency of harmonic generation depends onthe plasma temperature.